PERSEPSI MAHASISWA PAI TENTANG PROGRAM JUMAT MENGAJI UNTUK MENINGKATKAN KEMAMPUAN MEMBACA AL-QURAN - Hasbullah, Hasbullah; Marantika, Amelia; Azizah, Umamah (Universitas Cokroaminoto Yogyakarta, 2024)
This research aims to determine student perceptions regarding the Friday Koran program in the Islamic Religious Education department. This research was conducted on students spread across several semesters in the Islamic Religious Education department. The method used in this research is a qualitative method using a descriptive approach. disclosed are the data needed, phenomena related to the Friday Koran recitation program activities carried out by the Islamic Religious Education study program, students must be able to recite the Koran and read the Koran. The PAI department holds a Friday Koran recitation program spearheaded by students. The PAI study program does not require its students to take part in the program for the reason that they will develop awareness and sincerity. The results of this research are that students' perceptions are very good and their ability to read the Quran. Overall, the ability to read the Quran is very good and can improve students' learning abilities, because by reading the Al-Quran the mind becomes calm, a calm mind can bring good conditions. Study calmly so that the material given by the lecturer can be understood easily.